Femtosecond-assisted intracorneal ring segment complications in keratoconus: from novelty to expertise - Mounir A (Dove Medical Press, 2018)
Amr Mounir, Gamal Radwan, Mahmoud Mohamed Farouk, Engy Mohamed Mostafa Department of Ophthalmology, Faculty of Medicine, Sohag University, Sohag, Egypt Objectives: To document the difference between complication rate in the early curve of practicing intracorneal stromal rings and after gaining experience. Patients and methods: A retrospective study of 623 eyes of 417 patients with keratoconus who underwent Keraring implantation using femtosecond laser for channel creation. Results: The main outcome measures were reported intraoperative and postoperative complications. The overall complication rate was 12.7% (79 eyes) over the 4 years with 34 eyes in the first year (5.5%) and six eyes in the fourth year (0.96%). Over the 4 years of our practice, intraoperative complications were 7.1% and postoperative complications were 5.6%. Yet, there was a significant difference in intraoperative complications between the first and the fourth year where it was 3.5% and 0.48%, respectively. This also applies to the postoperative complication rate, which decreased from 1.9% to 0.5% in the fourth year. Conclusion: Complications with femtosecond-assisted intracorneal stromal ring procedure can be reduced by experience, making this procedure a safe and effective means of treating keratoconus. Yet, there are some complications that cannot be avoided such as sterile keratitis. Keywords: femtosecond laser, intracorneal rings, Kerarings, keratoconus